A rapid qualitative analysis of health care worker and community focus groups on determinants and implementation strategies for long-acting PrEP in antenatal and postpartum settings in Kenya - Tessa Concepcion; Marin Strong; John Kinuthia; Felix A. Otieno; Eunita Akim; Helen Aketch; Laurén Gómez; Grace John-Stewart; Bih Moki Suh; Nancy Ngumbau; Emmaculate M. Nzove; Jerusha N. Mogaka; et al. (Discover Health Systems, 2026)
Abstract Background New long-acting (LA-) PrEP modalities have demonstrated efficacy in HIV prevention and growing evidence of safety during pregnancy and lactation. There are unique considerations for LA-PrEP implementation in reproductive health settings, yet scarce implementation data are available. We identified potential barriers and facilitators and strategies for LA-PrEP implementation for pregnant and postpartum women. Methods We conducted a qualitative study using focus group discussions (FGDs) with healthcare workers (HCW) at five clinics and community advisory board (CAB) members related to PrEP delivery for pregnant and postpartum women. Interview guides were informed by the EPIS and CFIR frameworks. HCW FGDs included an activity to prioritize information, training, or support strategies for LA-PrEP provision. We used a rapid qualitative analysis to identify facilitators and barriers to integrating LA-PrEP into reproductive health settings and matched potential implementation strategies. Results A total of 9 FGDs were conducted with 45 individuals between August and October 2023 (5 FGDs among HCWs and 4 among CAB members). They identified interconnected determinants including training, funding, personnel, and community sensitization. Some strategies clearly addressed barriers (e.g. ongoing training to target access to knowledge). However, some barriers had no clear solution, such as LA-PrEP drug availability and access to funds to conduct training and community sensitization. The prioritization activity revealed common resources needed for LA-PrEP implementation (e.g., national guidelines, training, and personnel), but importance varied by location. A wide range of implementation strategies were identified, such as financial incentives for transportation, using community health providers to conduct community sensitization, and integrating LA-PrEP into family planning clinics. Conclusions HCW and CAB members were optimistic about the promise of new LA-PrEP options and identified important barriers and strategies for consideration. Future research should consider prioritizing implementation strategies and evaluating the impact of strategies on implementation barriers. This study emphasizes the importance and potential impact of offering LA-PrEP options to pregnant and postpartum women.